Indigenous Inuit Law, “Western” Law and Northern Issues - Loukacheva, Natalia (Arctic Review on Law and Politics, 2012)
The magnitude of rapid changes occurring in the Arctic have generated a further inquiry on the role of law and existing legal systems in meeting the many challenges that Northerners, Arctic indigenous peoples and their communities are facing today. On the one hand, we deal with the pluralism of legal orders across the Circumpolar Region which can be valuable to finding innovative solutions for existing issues, and it can be of learning significance to different Arctic jurisdictions. On the other hand, the dominating influence of national legal systems and legal procedures on the regulation of internal and local affairs of the Arctic sub-national entities and their communities raises the question of the role of indigenous legal traditions and practices in various Northern issues and developments. By looking mainly at the example of the Inuit of Canada’s Eastern and Central Arctic (Nunavut), to understand the Inuit law-ways, at the outset, this essay examines some general features of the traditional Inuit legal order. Further, by exploring some principles and aspects that define linkages and interactions between indigenous legal practices and “Western” law in the Arctic, it raises questions that are essential to our better understanding of the value of indigenous law in contemporary issues and developments in the North.Keywords: Indigenous law, Inuit law, legal pluralism, the ArcticCitation: Arctic Review on Law and Politics, vol. 3, 2/2012 pp. 200–217. ISSN 1891-6252